Classical and New Pharmaceutical Uses of Bacterial Penicillin G Acylase - Cobos-Puc, Luis; Rodríguez-Herrera, Raúl; Cano-Cabrera, Juan C.; Aguayo-Morales, Hilda; Silva-Belmares, Sonia Y.; Gallegos, Adriana C.F.; Hernández, José L.M. (Current Pharmaceutical Biotechnology, 2020)
Background: β-lactam antibiotics are the most used worldwide for the treatment of bacterial infections. The consumption of these classes of drugs is high, and it is increasing around the world. To date, the best way to produce them is using penicillin G Acylase (PGA) as a biocatalyst. Objective: This manuscript offers an overview of the most recent advances in the current tools to improve the activity of the PGA and its pharmaceutical application. Results: Several microorganisms produce PGA, but some bacterial strains represent the primary source of this enzyme. The activity of bacterial PGA depends on its adequate expression and carbon or nitrogen source, as well as a specific pH or temperature depending on the nature of the PGA. Additionally, the PGA activity can be enhanced by immobilizing it to a solid support to recycle it for a prolonged time. Likewise, PGAs more stable and with higher activity are obtained from bacterial hosts genetically modified. Conclusion: PGA is used to produce b-lactam antibiotics. However, this enzyme has pharmaceutical potential to be used to obtain critical molecules for the synthesis of anti-tumor, antiplatelet, antiemetic, antidepressive, anti-retroviral, antioxidant, and antimutagenic drugs.
Keywords: β-lactam antibiotics